Chemical and mechanical characterization of hyaluronic acid hydrogel cross‐linked with polyethylen glycol and its use in dermatology. Issue 4 (1st July 2020) - Zerbinati, Nicola; Esposito, Cristina; Cipolla, Giovanna; Calligaro, Alberto; Monticelli, Damiano; Martina, Virginia; Golubovic, Masa; Binic, Iva; Sigova, Julia; Gallo, Anna L.; D'Este, Edoardo; Jafferany, Mohammad; et al.
Abstract: Hydrogels based on hyaluronic acid are used to restore volume, hydration, and skin tone, as well as to correct scars, asymmetries or defects of the soft tissue. Hyaluronic acid is often chemically crosslinked with different crosslinking agents in order to improve its mechanical and biological properties. Here we focused on defining the chemical and mechanical characterization of a new hydrogel with specific characteristics: hyaluronic acid polyethylene glycol (PEG)‐crosslinked with a high concentration of hyaluronic acid (28 mg/mL), manufactured by MatexLab Spa, via Carlo Urbani 2, ang Via Enrico Fermi, Brindisi, Italy. We made a quantitative and qualitative analysis of the content of sodium hyaluronate in the hydrogel after polymerization and sterilization processes and also evaluated histologically the bio integration of these hydrogels in the cutaneous soft tissues. The results suggest that hyaluronic acid hydrogel PEG‐crosslinked have great bio integration, great chemical and mechanical properties, compared with other products available on the market, that are cross‐linked with different cross‐linking agents. The nontoxicity and nonimmunogenicity of PEG guarantee the lack of allergic and immunological reactions. The PEG‐crosslinking technology guarantees a high duration time of the implanted hydrogel because of more resistant physiological degradation.